Pemanfaatan Limbah Organik Rumah Tangga Untuk Budidaya Maggot di Desa Kedungwaringin Kabupaten Bekasi - Daspar, Daspar; Tim Mahasiswa KKN (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
Waste management in a number of areas in the country is still limited and is still a problem for the environment. One way to manage waste is by using it as a medium for cultivating BSF maggot flies (black soldier flies). That's why the Pelita Bangsa University KKN is carrying out a business cultivating BSF fly maggots in Kedung Waringin Village. The aim of this program is to empower village residents to process organic waste by cultivating BSF fly maggots into animal feed. The method of implementation is by conducting outreach or outreach in front of local community leaders and directly constructing BSF fly cages. The result of this activity is that animal feed is produced in the form of BSF fly maggots and organic fertilizer in packaged form ready for market. The results of monitoring and evaluation also show that there is positive enthusiasm from residents to carry out maggot cultivation.